Assessment of Cryptococcal Meningitis Concurrent with Multidrug-Resistant Tuberculous Meningitis: A Case Report - Elsadai, Elsadai; Priambodo, Ayu Prawesti; Mirwanti, Ristina; Sesilia, Fitri; Heriyansyah, Heriyansyah (Indonesian Journal of Global Health Research, 2024)
Cryptococcal meningitis is an infection that attacks the tissue lining the brain and spinal cord, caused by the fungus Cryptococcus neoformans. This infection mainly occurs in individuals with a weakened immune system, such as people with HIV/AIDS. The spread of this fungus into the central nervous system can result in serious conditions, even fatal if not treated quickly and appropriately. Objective: to present a rare and complex case report of a patient with concurrent cryptococcal meningitis and multiresistant tuberculous meningitis, as well as evaluate the management strategies used in the patient's care. Method: Case study was conducted through a comprehensive approach including health history assessment, physical examinations, psychosocial analysis, customized nursing assessment forms, electronic medical record reviews, laboratory diagnostics, imaging studies, and multidisciplinary consultations to ensure accurate diagnosis and effective interventions Mrs. R, a 33 year old woman with a final diagnosis including Pneumonia with aspiration mechanism, Cryptococcal Meningitis, Grade II MDR TB Meningitis complicated by arteritis, as well as several other conditions including Hyponatremia, hypochloremia, and hypocalcemia due to insufficient intake, Chronic Suppurative Otitis Media (CSOM) and Typhoid Fever. Results: The patient was diagnosed with aspiration pneumonia, cryptococcal meningitis, multiresistant tuberculous meningitis, as well as other conditions such as hypernatremia, hypokalemia, hypocalcemia, chronic suppurative otitis media, and typhoid fever. Despite treatment, the patient's condition worsened, leading to respiratory failure and death from aspiration pneumonia. Conclusions: This case report highlights the diagnostic and therapeutic challenges in managing concurrent cryptococcal meningitis and multiresistant tuberculous meningitis. This emphasizes the importance of a comprehensive approach in diagnosis and management in patients with complex concurrent infections, even without HIV. This case also emphasizes the need for further research and improved strategies for managing rare and complex infections such as this.